Computational Methods of Multi-Physics Problems - Rabczuk, Timon (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book offers a collection of six papers addressing problems associated with the computational modeling of multi-field problems. Some of the proposed contributions present novel computational techniques, while other topics focus on applying state-of-the-art techniques in order to solve coupled problems in various areas including the prediction of material failure during the lithiation process, which is of major importance in batteries; efficient models for flexoelectricity, which require higher-order continuity; the prediction of composite pipes under thermomechanical conditions; material failure in rock; and computational materials design. The latter exploits nano-scale modeling in order to predict various material properties for two-dimensional materials with applications in, for example, semiconductors. In summary, this book provides a good overview of the computational modeling of different multi-field problems.
English
Keywords: temperature variation; h-BN and Graphene sheets; molecular dynamics simulation; thermal conductance; mechanical; patch repair; first-principles; finite element method; Von Mises stress; composite; thermal; electrofusion socket joints; two-dimensional semiconductor; buried gas distribution pipes; level set technique; lithium-ion battery; phase field approach to fracture; meshless method; rock mechanics; fracture of geo-materials; flexoelectricity; pressure gradient effect; medium density polyethylene (MDPE); high density polyethylene (HDPE); size effect; fracture analysis; interface modeling; cohesive zone model; thermal conductivity; peridynamics